Upaya Meningkatkan Kemampuan Kognitif Melalui Media Pelangi Dalam Gelas Pada Anak Usia 5-6 Tahun di RA Ubay Bin Ka’ab Salo - Nurmala Dewi; Melvi Lesmana Alim; Putri Asilestari (Jurnal Pendidikan Tuntas, 2024)
This research was motivated by the low cognitive abilities of children at RA Ubay Bin Ka'ab Salo. Based on observations made in the field on several indicators, cognitive development in children is not yet optimal due to several factors such as the activities carried out to improve children's cognitive abilities are less varied. One solution to overcome this problem is to use rainbow media in glass. The aim of this research is to find out whether rainbow media in a glass can improve cognitive abilities in children aged 5-6 years at RA Ubay Bin Ka'ab Salo. This research was conducted using the classroom action research method. The data collection techniques used were observation, documentation and assessment. The research was conducted using two learning cycles. The results of the research showed that there was an increase in each cycle carried out. The child's cognitive ability in the initial condition was 60%, and in the first cycle it increased to 78.66%. Furthermore, in cycle II it increased to 98.66%. These results show an increase in children's cognitive abilities through walking color games in children aged 5-6 years at RA Ubay Bin Ka'ab Salo. Keywords: Cognitive Ability, Rainbow Colors, Media